In-vitro responses of peritoneal macrophages of marine red hybrid tilapia (Oreochromis spp.) model to vibriosis: A comparative study between vaccinated and non-vaccinated fish - Manchanayake, Tilusha; Md Yassin, Ina Salwany; Azmai, Mohammad Noor Amal; Saad, Mohd Zamri; Nawi, Mohd Firdaus; Salleh, Annas (2022)
Vibriosis, an infection caused by Gram-negative bacteria of the genus Vibrio is a major disease in global aquaculture. Vaccination is an effective preventive measure against vibriosis. Phagocytosis, the fundamental cellular mechanism that eliminates invading pathogens is governed by phagocytic cells like macrophages and neutrophils. To gain insight into the mechanism of vaccination and its role in influencing macrophage activity in reducing the number of live Vibrio species prior to the establishment of infection in the host, in vitro responses of peritoneal macrophages of vaccinated and unvaccinated marine red hybrid tilapia were compared in terms of phagocytosis, intracellular killing, and macrophage death rates. A total of 90 healthy marine red hybrid tilapia were divided into three equal groups. Group 1 and 2 were vaccinated using feed-based oil-adjuvanted and non-adjuvanted killed whole cell V. harveyi vaccine, respectively. Group 3 was not vaccinated. Vaccine feed was given on weeks 0, 2 and 6. Peritoneal macrophages were collected at week 0 and 10. Macrophages were exposed to V. harveyi or V. alginolyticus and harvested at 0-, 30-, 60- and 120-minutes post-infection. The rate of phagocytosis, intracellular killing rate of bacteria and rate of macrophage cell death were calculated. In general, post-vaccinated macrophages of all treatment groups showed a significant (p<0.05) increase in phagocytosis than pre-vaccinated macrophages following V. harveyi and V. alginolyticus challenge. Macrophages of post-vaccine oil-adjuvanted group showed significant (p<0.05) increase in intracellular killing of V. harveyi and V. alginolyticus. Macrophages of post- vaccinated Group 2 fish showed a higher cell death rate following V. harveyi and V. alginolyticus infection than that of post-vaccinated Group 1 fish. This study proved that the macrophages of tilapia immunized with an oil-adjuvanted vaccine were more efficient in phagocytosis, intracellular killing, and more resistance compared to non-adjuvanted vaccinated and unvaccinated tilapia in the presence of V. harveyi or V. alginolyticus.